2016
DOI: 10.1111/ijd.13102
|View full text |Cite
|
Sign up to set email alerts
|

Increased MicroRNA‐1266 levels as a biomarker for disease activity in psoriasis vulgaris

Abstract: miR-1266 may have an important role in the pathogenesis of psoriasis vulgaris. This may presumably have possible future implications on the treatment of this chronic disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 37 publications
(53 reference statements)
0
7
0
Order By: Relevance
“…One of the most important findings in this work is the positive correlation between PB IFN- γ + Th17 cells and the PASI score, which indicates that these cells are associated with the severity. In psoriasis, the existence of biomarkers associated with severity, such as IL-36 γ , Squamous Cell Carcinoma Antigen 2 (SCCA2), and miRNA1266, has been reported [ 56 58 ]. To our knowledge, this is the first report of a Th17 cells subset associated to the severity of psoriasis.…”
Section: Discussionmentioning
confidence: 99%
“…One of the most important findings in this work is the positive correlation between PB IFN- γ + Th17 cells and the PASI score, which indicates that these cells are associated with the severity. In psoriasis, the existence of biomarkers associated with severity, such as IL-36 γ , Squamous Cell Carcinoma Antigen 2 (SCCA2), and miRNA1266, has been reported [ 56 58 ]. To our knowledge, this is the first report of a Th17 cells subset associated to the severity of psoriasis.…”
Section: Discussionmentioning
confidence: 99%
“…miRNA plays an important role in posttranscriptional regulation of gene expression, participating in many important physiological processes, including development, cell differentiation, and regulation of signaling pathways [ 55 ]. The participation of these molecules is emphasized in pathological conditions, for example, in tumors [ 55 , 56 ], neurological disorders [ 56 ], and psoriasis [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…The high serum level of miR-1266 was observed in patients with psoriasis, highlighting its potential use as a biomarker [ 18 ]. In addition, the increased expression of miRNA-155, let-7i, miRNA-146a, miRNA-21, and miRNA-223 in the mononuclear cells of peripheral blood and also miRNA-21, miRNA-146a, and miRNA-223 in plasma was noted [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…The differentially expressed miRNAs we identified do not correspond to those of other studies in psoriasis, and a possible explanation of the discrepancy is that most of the previous studies used samples such as psoriatic lesion tissues, keratinocytes, hair roots/shaft, PBMCs, psoriasis epidermal cells, and dermal T cells, but not plasma [ miR-1266 and miR-33 have been detected to be deregulated in blood samples of patients with psoriasis. miR-1266 is overexpressed in psoriasis serum samples [77], which may be differentially expressed in plasma. In addition, since miR-33 is involved in the posttranscriptional regulation of genes associated with lipid metabolism, one study reported that the plasma levels of lipid and glucose metabolismrelated miR-33 are increased and correlated with insulin in psoriasis patients [78].…”
Section: Journal Of Immunology Researchmentioning
confidence: 99%